UNDERSTANDING VOLUNTARY DISCLOSURES IN AUSTRALIA - Aripin, Norhani; Tower, Greg; Taylor, Grantley (The journal of contemporary issues in business and government, 2009)
This study provides preliminary analysis of the extent and quality of financial ratio disclosures in the 2007 annual reports of Australian listed companies. The extent of financial ratio disclosures is captured through a 43 item template. In addition a unique 16 item matrix, evolved from the International Accounting Standards Board’s conceptual framework to measure the quality of financial ratio disclosures, is developed. The extent of financial ratios by Australian firms is a surprisingly low 9.2 percent. Shareholders return and return on equity ratios were reported by at least half of the companies yet 16 other ratios had zero communication. The quality of the financial ratios is rated somewhat better with reliability tenets best presented and comparability issues the worst. Resource firms tended to have the lowest quality of disclosure. Consistent with agency theory, statistical analysis shows that larger firms—those with a higher proportion of independent directors and entities that have a higher proportion of independent auditors—are likely to disclose financial ratio information more extensively. The findings of this research have important implications for understanding managerial disclosure incentives as they relate to the extent and quality of financial ratio disclosures in Australia. Economic drivers seem to better explain extent than the inherent quality of such communication.